Development and Utility of Quality Metrics for Ambulatory Pediatric Cardiology in Kawasaki Disease. (March 2020) - Teitel, David F.; Newburger, Jane W.; Sutton, Nicole; Tani, Lloyd Y.; Harahsheh, Ashraf S.; Jone, Pei-Ni; Mensch, Deborah J.; Cotts, Timothy; Davidson, Alex; Dahdah, Nagib; Johnson, Walter H.; Portman, Michael A.
The Adult Congenital and Pediatric Cardiology (ACPC) Section of the American College of Cardiology sought to develop quality indicators/metrics for ambulatory pediatric cardiology practice. The objective of this study was to report the creation of metrics for patients with Kawasaki disease. Over a period of 5 months, 12 pediatric cardiologists developed 24 quality metrics based on the most relevant statements, guidelines, and research studies pertaining to Kawasaki disease. Of the 24 metrics, the 8 metrics deemed the most important, feasible, and valid were sent on to the ACPC for consideration. Seven of the 8 metrics were approved using the RAND method by an expert panel. All 7 metrics approved by the ACPC council were accepted by ACPC membership after an "open comments" process. They have been disseminated to the pediatric cardiology community for implementation by the ACPC Quality Network.